Improvements in tooth brushing behavior in children with autism spectrum disorder using mobile dentistry game application: study experimental - Putri, Tarisya Permata; Suwargiani, Anne Agustina; Sasmita, Inne Suherna; Sukmasari, Susi (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by abnormalities in social interaction, limited interests, and repetitive habits. ASD children have motor, sensory, and communication limitations and difficulties that affect daily activities, namely brushing teeth, therefore education is needed to improve the tooth brushing behavior of ASD children. Education can use the Mobile Dentistry Game Application, namely Pokémon Smile which is one application that can be used to help increase knowledge and education of children with ASD in brushing teeth. The purpose of the study was to analyze improvement  in the tooth brushing behavior of children with ASD using the mobile dentistry game application. Methods: A quasi-experimental study with 16 children was conducted in November 2024. The study consisted of measuring tooth brushing behavior before using Pokémon Smile, followed by using the game and measuring tooth brushing behavior after using the game. Results: There was a significant change with a p-value (p<0.05) 0.004. The average score of children's tooth brushing behavior before the use of Pokémon Smile was 5.25 with most behavior levels being very poor and after the use 6.86 with most behavior levels being moderate. There was an increase in the mean score of tooth brushing behavior by 17.05, reflecting a change in the level of tooth brushing behavior of ASD children from the poor category to moderate. Conclusion: Tooth brushing behavior of children with autism spectrum disorder (ASD) using a mobile dentistry game application has improved. This improvement is reflected in positive behavioral changes observed after using the application. KEY WORDS: mobile dentistry game application, health app, visual pedagogy, tooth brushing behavior, autism spectrum disorder, childrenPerilaku menyikat gigi pada anak gangguan spektrum autisme menggunakan mobile dentistry game application: studi eksperimentalABSTRAKPendahuluan: Gangguan Spektrum Autisme (GSA) merupakan gangguan neurodevelopmental yaitu gangguan perkembangan saraf  yang memiliki ciri khas berupa kelainan pada interaksi sosial serta minat yang terbatas dan kebiasaan yang repetitif atau berulang. Anak GSA memiliki keterbatasan dan kesulitan motorik, sensorik, dan komunikasi yang mempengaruhi kegiatan sehari-hari diantaranya menyikat gigi sehingga diperlukan edukasi untuk meningkatkan perilaku menyikat gigi anak GSA. Edukasi dapat menggunakan Mobile Dentistry Game Application, yaitu Pokémon Smile yang merupakan salah satu aplikasi yang dapat digunakan untuk membantu meningkatkan pengetahuan serta edukasi anak dengan ASD dalam menyikat gigi. Tujuan penelitian adalah menganalisis perbaikan perilaku menyikat gigi anak dengan GSA menggunakan mobile dentistry game application. Metode: Penelitian berupa quasi eksperimental dengan sampel 16 anak telah dilaksanakan pada November 2024. Penelitian terdiri dari pengukuran perilaku menyikat gigi sebelum penggunaan Pokémon Smile, dilanjutkan dengan penggunaan permainan, dan pengukuran perilaku menyikat gigi setelah penggunaan permainan. Hasil: Terdapat perubahan signifikan dengan p-value (p<0,05) 0,004. Rerata skor perilaku menyikat gigi anak sebelum penggunaan Pokémon Smile 5,25 dengan mayoritas tingkat perilaku sangat buruk dan setelah penggunaan 6,86 dengan mayoritas tingkat perilaku menjadi cukup. Terdapat peningkatan rerata nilai perilaku menyikat gigi sebesar 17,05 mencerminkan adanya perubahan tingkat perilaku menyikat gigi anak GSA dari kategori buruk menjadi cukup. Simpulan: Perilaku menyikat gigi anak dengan Gangguan Spektrum Autisme (GSA) menggunakan mobile dentistry game application mengalami peningkatan. Peningkatan terlihat dari perubahan perilaku ke arah positif setelah menggunakan aplikasi. KATA KUNCI: mobile dentistry game application, visual pedagogi, perilaku menyikat gigi, gangguan spektrum autisme, anak